The paraphilias : changing suits in the evolution of sexual interest paradigms - Fedoroff, J. Paul (New York : Oxford University Press, 2019)
'The Paraphilias' examines current and past perspectives concerning unconventional sexual interests associated with both criminal and non-criminal activities. The text provides extensive case histories and tables summarizing over 100 paraphilias and the latest research regarding them. It also reviews diagnostic criteria for the paraphilias.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 1, 2019).
Keywords: Paraphilias; Psychosexual disorders